The Application of Habituality in Peruvian Criminal Legislation and Its Impact on the Presumption of Innocence - Bueno Flores, Lisdey Magaly (2025)
The concept of habituality provided for in Article 46-C of the Criminal Code has undergone a series of changes over the years, which indicates that the criminal policy promoted by the State has proven insufficient. Likewise, the application of this article has raised a number of problems, which is why, at the IV Jurisdictional Plenary of the Permanent, Transitory, and Special Criminal Chambers of the Supreme Court of Justice of the Republic, Plenary Agreement No. 1-008/CJ-116 was issued. This agreement establishes as binding case law that, for habituality to be established, no prior conviction—that is, no declaration of criminal liability—is required. However, over the course of these years, some justice system actors have taken the view that, for this legal concept to operate, it is not enough merely to commit an intentional offense in accordance with the terms of the agreement, but that a declaration of criminal liability is indispensable in order not to infringe the principle of the presumption of innocence. For these reasons, this article seeks to determine how Article 46-C of the Criminal Code, which regulates the legal concept of habituality, undermines the constitutional principle of the presumption of innocence, enshrined in Article 2, paragraph 24(e), of the 1993 Political Constitution.